О значении работ М. И. Стеблин-Каменского по истории древнескандинавской литературы - Смирницкая, О. А. (Kalbotyra, 1985)
In his works on Old Scandinavian literature Professor M. I. Steblin-Kamenskij set forth a new theory of the history of literature based on two main concepts: unconscious authorship and syncretic truth. He discusses from the historical point of view various genres of Old Icelandic literature, finding their place in the general picture of evolution.